Synthesis and characterization of a polyurethane carrier used for a prolonged transmembrane transfer of a chili pepper extract - Borcan LC (Dove Medical Press, 2018)
Livia-Cristina Borcan,1,* Zoltan Dudas,2,3,* Adel Len,2,4 Janos Fuzi,2,4 Florin Borcan,5 Mirela Cleopatra Tomescu1 1The 5th Department (Internal Medicine I), Faculty of Medicine, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 2Neutron Spectroscopy Department, Institute for Solid State Physics and Optics, Wigner Research Centre for Physics, Hungarian Academy of Sciences, Budapest, Hungary; 3Inorganic Department, Institute of Chemistry, Romanian Academy, Timisoara, Romania; 4Faculty of Engineering and Information Technology, University of Pécs, Pécs, Hungary; 5The 1st Department (Analytical Chemistry), Faculty of Pharmacy, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania *These authors contributed equally to this work Purpose: Red chili peppers have been highly valued in gastronomy and traditional medicine since ancient times; it seems that it is not just an ingredient for food but also a good remedy for various medical conditions such as increased blood pressure and high levels of serum triglycerides and cholesterol, myocardial infarction, arthritis, and migraines. The objective of this study is the characterization of a new carrier used for encapsulated extract. Methods: Chili pepper extract was obtained and was physically entrapped inside polyurethane microparticles in order to diminish the irritative potential of this extract. The particles were evaluated by Zetasizer measurements, small-angle neutron scattering and thermal analysis, scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy; the encapsulation efficacy and the drug release profile were assessed by UV-Vis spectroscopy. Bioevaluations on mice skin were performed to predict the irritative potential of the samples. Results: Two different types of samples were compared: hollow polyurethane microparticles vs polyurethane particles containing the natural extract. The sizes of the particles were very similar, but the sample containing the extract presents three particle populations (the polydispersity index increases from 0.3 to 0.6 from one sample to another). The zeta-potential measurements and SEM images indicate a medium tendency to form clusters, while the UV-Vis study revealed an almost 70% encapsulation efficacy. Conclusion: The results suggest that encapsulation of a chili pepper extract inside polyurethane microparticles leads to a non-irritative product with a prolonged release: ~30% of encapsulated extract is released within the first 8 days and a maximum 45% is reached in 2 weeks. Keywords: corneometry, drug delivery system, erythema, FTIR, SANS, UV-Vis, zeta-potential